The evolution of attitudes and approaches to occupational health and safety in New Zealand - Henderson, Barry (Massey University, 1995)
The contemporary expression "excellence" in Occupational Health and Safety is mere rhetoric without a genuine commitment by the parties to positive attitudes involving a meaningful desire to protect the worker. Regretfully, attitudes require stimulation and encouragement to ensure positive growth. One important catalyst for growth is a sympathetic political ideology. In a general sense, New Zealand enjoyed a sympathetic political ideology with the Liberal Government between 1891-1912. The legislation enacted during the first five years of the Liberal Administration was significant and far reaching. The legislative innovations witnessed the face of Industrial Relations being dramatically altered, the embryonic origins of the Department of Labour, the re-focusing of the Trade Union movement and a structure developed for the fledgling Inspectorate. During this era, New Zealand's political ideology was a mixture of socialism, liberalism and pluralism, and was coined as "the social laboratory" by a sceptical international audience. The legislative enthusiasm of the Liberal Administration was followed by a variety of political ideological that were essentially lacklustre in their focus upon Occupational Health and Safety. The casualty was the luckless worker confronted by a bewildering array of legislation that was confusing, heavily prescriptive and very often duplicating. Attitudes of the Inspectorate were confused due to the ill-defined focus and low morale. The Labour Government that was swept into power in July 1984 lacked a real political reforming conviction to alter the status quo and it was not until the National Government came to power in 1990 that dramatic change occurred. The National administration subscribing to a laissez faire doctrine scuttled a century's worth of prescriptive legislation and leaving the worker to fend for himself in a market driven environment, alienated from the hitherto trade union representative by the marginalisation focus of the Employment Contracts Act 1991. As such, the worker can be excused for interpreting the concept of "excellence" with some degree of scepticism.
Keywords: Industrial hygiene and safety; New Zealand; Government policy